Advances in immunotherapy for acute myeloid leukemia. (15th March 2018) - Przespolewski, Amanda; Szeles, Andras; Wang, Eunice S
Evasion of the host immune system is a key mechanism to promote malignant progression. Therapeutically targeting immune pathways has radically changed the treatment paradigm for solid and lymphoid tumors but has yet to be approved for myeloid malignancies. Here, we summarize the most recent advances in immunotherapy for acute myeloid leukemia. Topics reviewed here include adoptive cellular approaches (chimeric antigen receptor-T cells, natural killer and other immune cells), checkpoint inhibitors (anti-PD-1/PD-L1, anti-CTLA-4 and TIM-3) and vaccines (WT-1, HLA-A2 and hTERT). Emphasis is placed on agents with clear evidence of tumor-specific immune responses and/or clinical activity in early-phase trials. Despite concerns regarding heterogeneous antigen expression and cytokine release syndrome, immunotherapy remains a highly promising strategy for acute myeloid leukemia, particularly transplant-ineligible patients and minimal residual disease states.